Pencarian Informasi Kesehatan Ibu dan Anak Pada Masyarakat Miskin Penerima Manfaat Program Keluarga Harapan (PKH) - Ratna Frenty Nurkhalim; Indah Susilowati (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Background: Program Keluarga Harapan (PKH) is a priority program that is expected to improve the welfare of its beneficiaries. In the implementation, the PKH’s beneficiaries are required to attend family enhancement meeting activities (P2K2). Among all the information that must be given to P2K2, which one is needed and is in demand by the beneficiaries of PKH? Objectives: To know the needs of maternal and child health information in the PKH group of recipients. Method: We involved 76 PKH beneficiaries and asked them to fill our questionnaire. The questionnaire consists of 12 questions about what kind of health information they need and how to obtain it. Sampling techniques use is simple random sampling. Result: There are some KIA information needs sought by the KPM. But the greatest need is information about the KB. Information search is done by asking directly to the local midwife's conclusion: PKH escorts need to establish good cooperation with midwives and master the information about the KB because it is tasked to deliver it to the PKH beneficiaries through P2K2 activities.